Comparative Analysis of Arabic Linguistic Development in West Asia and Southern Europe - Achmad, Syauqi Amirudin (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
It is widely known that a science is always dynamic (developing), as is the case with Arabic linguistics. It is also important to note that each region experiences different developments, even within the same discipline. Similarly, Arabic linguistics has experienced different developments in Asia and Europe. This article aims to provide information or a historical account of the development of Arabic linguistics in Asia and Europe over time. This article will explore the secrets of history, events, and comparisons between the development of Arabic linguistics in Asia and Europe. The research method used in this article is qualitative-descriptive. This article draws data from several papers, articles, and theses from various available journals. This method was chosen for several compelling reasons: first, all data presented in this article can be authenticated; second, readers will gain a broader understanding of the research findings of experts in the history of Arabic linguistics in Asia and Europe; and third, it will help avoid errors in data collection. Therefore, this article chooses a qualitative-descriptive method to analyze the development of Arabic linguistics in Asia and Europe. The expected outcome of this research is that readers will be able to understand and understand the dynamics of Arabic linguistics, its ups and downs in Asia and Europe.